Usability Study of Dehy Pro (Dehydration Prevention) Application to Prevent Diarrhea Dehydration among Children in Jember - Lailil Fatkuriyah; Ainul Hidayati; Wike Rosalini (PROFESSIONAL HEALTH JOURNAL, 2024)
Introduction: Diarrhea is preventable yet in Indonesia, it is still the second leading cause of under five’s death. Dehydration is the main factor in most diarrhea-related fatalities in children. There is a requirement for health education initiatives that prioritize the prevention of diarrhea dehydration through the utilization of mobile health applications. Objectives: This study aimed to evaluate the usability and acceptance of Dehy Pro Application in preventing diarrhea dehydration among children in Jember. Methods: This study involved 56 respondents consisting of 6 experts and 50 mothers with children under five. Mothers were gathered using purposive sampling. Application development is carried out through several stages, including a literature study, design stage, development stage, and dissemination stage. The usability of Dehy Pro was assessed using the Mobile Application Usability Questionnaire (MAUQ). Results: The three items with the highest mean according to the expert's assessment were "The app was easy to use" (6.85/7), "It was easy for me to learn to use the app" (6.85/7), and "The app would be useful for my health and wellbeing" (6.85/7). Meanwhile, according to the respondent's assessment, there were four items with the highest mean, including "The app was easy to use" (6.94/7), "It was easy for me to learn to use the app" (6.92/7), "I would use this app again" (6.92/7), and "The app helped me manage my health effectively" (6.92/7). Conclusions: Dehy Pro as an application to increase the role of parents in preventing diarrhea dehydration in children has good usability and acceptance although it still needs some improvements.